Mineral Composition Analysis Of Malaysian Sulphide Gold Ore_Mineral Composition Analysis Of Malaysian Sulphide Gold Ore - Safri, Mohammad Hafizuddin Mohd (Universiti Sains Malaysia, 2017)
In this study, the Buffalo Reef situated at the Selinsing district is famous with the occurrence of gold ore near the Central Belt of Peninsular Malaysia. The mineralogy and paragenesis of ore deposit is main idea for establish better mineral processing for gold processing. The objective of this research is focus into determination of mineral composition and mineral phase of Sulphide ore samples from different location in Buffalo Reef. Besides that, the sampling is done at the North and South of Buffalo Reef by grab sampling method. Mineral phase analysis is done using the analytical method after the ore preparation using XRD. Mineral composition is study using XRF and determination of particle size distribution after the sieve for each of samples. The morphology study is done via the study of polish section for SEM and optical microscope. The optimum of milling parameter is investigated via the experimental work using DOE of MINITAB using two different type of sample The liberation of mineral sulphide is determine by using the image analyzer, Image J to calculate the threshold value.